THE IMPACT OF FISCAL POLICY TOOLS ON AGRICULTURAL PRODUCTION: TÜRKIYE AS A MODEL - Ahmed Albajjari; Ahmed Abdul-Majeed; Mohammed Albana (Mesopotamia Journal of Agriculture)
The agricultural sector in developing countries (including Iraq) faces inefficient financial policies that have led to low levels of agricultural production and their inability to achieve food security for their citizens, especially the fiscal policy is an effective tool in achieving balanced growth and enhancing the economic performance of economic sectors, including the agricultural sector, as it is one of the strategic sectors. Because of its ability to achieve food security and support the level of economic performance in both developing and developed economies. The success of the experience of the Republic of Turkey, in which the agricultural sector represents one of the basic pillars of the Turkish economy during the initial stages of economic development and its high contribution to the gross domestic product and the agricultural workforce. It invited us to analyze the mechanisms of the impact of fiscal policy on the Turkish economy and its role in stimulating the economic performance of this sector, and its ability to support agricultural exports during the period 1999-2022, and the extent to which it can be adopted as a roadmap for the impact of financial policies on agricultural production in developing economies (including the Iraqi economy). The results of the study showed that there is a significant and positive relationship between the variables of government spending on the agricultural sector, the total credit granted to the agricultural sector, and the total formation of fixed capital for the agricultural sector as independent variables in their impact on the dependent variable (agriculture production) in the long term during the study period. Despite the differences in the nature of the economic and environmental conditions between Turkey and Iraq, the study suggests adopting the Turkish model of fiscal policy in supporting the agricultural sector as an incentive policy to increase agricultural production and achieve food security in Iraq.